2013
DOI: 10.1001/jamaoto.2013.3297
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Cautery and Adverse Affects on Cochlear Implants<alt-title>Monopolar Cautery &amp; Adverse Affects on Cochlear Implants</alt-title>

Abstract: Monopolar cautery did not produce detectible damage to any of the cochlear implant devices or produce detectible temperature change in the cochlea at low or high levels of cautery in the oral cavity in this experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…MES applied to the adenoid of implanted cadaveric pigs at a setting of 50 (double the normal intensity) for 15 min failed to produce any damages upon manufacturer testing of the CI 4 . Similarly, no adverse effects were noted in CI devices on manufacturer testing after MES was applied at up to 50 W for up to 30 min to the abdomen and tongue of two fresh human cadavers 6 . Even with application of MES at up to 100 W for 1 min to a location as close as the ipsilateral temporalis muscle immediately overlying a CI in a fresh human cadaver, manufacturer testing noted no damage to the implant 5 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…MES applied to the adenoid of implanted cadaveric pigs at a setting of 50 (double the normal intensity) for 15 min failed to produce any damages upon manufacturer testing of the CI 4 . Similarly, no adverse effects were noted in CI devices on manufacturer testing after MES was applied at up to 50 W for up to 30 min to the abdomen and tongue of two fresh human cadavers 6 . Even with application of MES at up to 100 W for 1 min to a location as close as the ipsilateral temporalis muscle immediately overlying a CI in a fresh human cadaver, manufacturer testing noted no damage to the implant 5 .…”
Section: Discussionmentioning
confidence: 85%
“…4 Similarly, no adverse effects were noted in CI devices on manufacturer testing after MES was applied at up to 50 W for up to 30 min to the abdomen and tongue of two fresh human cadavers. 6 Even with application of MES at up to 100 W for 1 min to a location as close as the ipsilateral temporalis muscle immediately overlying a CI in a fresh human cadaver, manufacturer testing noted no damage to the implant. 5 However, in the dental study noted previously, the combination of maximum electrosurgical unit device energy output and the use of a mode applying unidirectional electrical current resulted in "irrevocable damage" to the CI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This can cause damage to the device or to the auditory neurons where the electrode inserts. 17 In a cadaver study, Jeyakumar et al found that cochlear implants had no electrical damage from electrocautery tested up to levels of 100 W, well above usages in orthopaedic surgery which typically do not exceed 50 W. 18,19 Manufacturer's safety guidelines for surgical procedures warn that monopolar is safe to use on the trunk and limbs but should not be used on the head and neck. Bipolar instruments may be used in this area, though should not be used within 2 cm of the electrodes.…”
Section: Nonorthopaedic Devicesmentioning
confidence: 99%